Impact of Investment Diversification on Profitability of Nepalese Commercial Banks - Gomden, Sushma Tamang; Chaudhary, Susmita; Koirala, Susmita; Acharya, Usha; Ojha, Yubraj (Nepalese Journal of Economics, 2024)
This study examines the impact of investment diversification on the profitability in the context of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are investment on securities, bank capital, loan portfolio, deposit by customer, non-interest income and bank size. The study is based on secondary data of 16 commercial banks with 112 observations for the period from 2016/17 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of investment diversification on the profitability of Nepalese commercial banks. The study showed that bank capital has a positive impact on return on assets. It means that increase in bank capital leads to increase in return on assets. Similarly, loan portfolio has a positive impact on return on assets and return on equity. It shows that increase in loan portfolio leads to increase in return on assets and return on equity. Moreover, deposit by customer has a positive impact on return on assets and return on equity. It indicates that increase in deposit by customer leads to increase in return on assets and return on equity. In addition, non-interest income has a positive impact on return on assets and return on equity. It shows that higher the non-interest income, higher would be the return on assets and return on equity. In contrast, investment on securities has a negative impact on return on assets and return on equity. It indicates that increase in investment on securities leads to increase in return on assets and return on equity. In addition, the study shows that bank size has a positive impact on return on assets and return on equity. It indicates that increase in bank size leads to increase in return on assets and return on equity.